The Influence of Digital Competency, Employee Engagement, and Leadership Style on SME Employee Performance in Indonesia: Innovation Capability as A Mediator and Organizational Culture as A Moderator in the Society 5.0 Era - Tiong, Piter; Sumaryo, Partono; Simamora, Siti Aisyah Putri (National Research and Innovation Agency, Indonesia, 2024)
This study investigates the impact of digital competency, employee engagement, and leadership style on employee performance in Indonesian SMEs, framed within the Society 5.0 era. The study uniquely incorporates innovation capability as a mediator and organizational culture as a moderator, exploring how these factors enhance performance and innovation in a digitally advancing society. Using a quantitative approach and data from 350 SME employees, the findings demonstrate that digital competency, engagement, and leadership style significantly influence performance. Moreover, innovation capability mediates these relationships, while a supportive organizational culture strengthens the link between these factors and innovation. This study’s novel approach provides valuable insights into HRM strategies, emphasizing the need for ongoing digital skill development, engaged leadership, and adaptive cultural practices to drive resilience and innovation in SMEs. These findings contribute to the broader understanding of effective performance enhancement practices in the Society 5.0 context, providing actionable recommendations for SME managers.